A Liquid-Handling Robot for Automated Attachment of Biomolecules to Microbeads. (August 2016) - Enten, Aaron; Yang, Yujia; Ye, Zihan; Chu, Ryan; Van, Tam; Rothschild, Ben; Gonzalez, Francisco; Sulchek, Todd
Diagnostics, drug delivery, and other biomedical industries rely on cross-linking ligands to microbead surfaces. Microbead functionalization requires multiple steps of liquid exchange, incubation, and mixing, which are laborious and time intensive. Although automated systems exist, they are expensive and cumbersome, limiting their routine use in biomedical laboratories. We present a small, bench-top robotic system that automates microparticle functionalization and streamlines sample preparation. The robot uses a programmable microcontroller to regulate liquid exchange, incubation, and mixing functions. Filters with a pore diameter smaller than the minimum bead diameter are used to prevent bead loss during liquid exchange. The robot uses three liquid reagents and processes up to 10 7 microbeads per batch. The effectiveness of microbead functionalization was compared with a manual covalent coupling process and evaluated via flow cytometry and fluorescent imaging. The mean percentages of successfully functionalized beads were 91% and 92% for the robot and manual methods, respectively, with less than 5% bead loss. Although the two methods share similar qualities, the automated approach required approximately 10 min of active labor, compared with 3 h for the manual approach. These results suggest that a low-cost, automated microbead functionalization system can streamline sample preparation with minimal operator intervention.